A review paper on effect of input welding process parameters on structure and properties of weld in submerged arc welding process. (2020) - Sharma, Harsh; Rajput, Balram; Singh, Rudra Pratap
Abstract: Joining of materials with the help of submerged arc welding machine is widely used in the concerned industries. The quality of the weld is identified by several welding output parameters like weld width, re-inforcement height, depth of penetration, hardness, impact strength and tensile strength etc. The input welding parameters on which outputs depend are welding current, voltage, feed rate, speed of welding, electrode extension, diameter of electrode and electrode angle etc. All the researchers try to optimize these parameters according to the concerned requirement. In this review paper it was tried to consider different research papers containing the research and analysis made on input output parameters of submerged arc welding process. This paper also focused on analysis of some research papers containing heat input rate, cooling rate of weld, micro structure of weld and heat affected zone and their effect on the performance of the joint. Total 28 research papers were selected for our consideration after a thorough investigation of several such papers. After the analysis of the research papers the future scope of research was also suggested.